The Effect of Using Flight Information Display System, Boarding Lounge Facilities, and Service Quality in Increasing Passenger Satisfaction at Terminal 2 of Soekarno Hatta Airport - Tito Warsito; Nashrullah Nashrullah; Aryo Bagus Prasetya; Ichsanul Amal (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to investigate the effect of FIDS (X1), boarding lounge facilities (X2), and service quality (X3) on the level of passenger satisfaction (Y) at Terminal 2 of Soekarno-Hatta Airport. The research method used is quantitative. Data was collected through a survey method with the distribution of questionnaires, as many as 105 respondents who were airport passengers were the subjects of the study. Data analysis using multiple statistical techniques, reliability tests, validity tests, normality tests, determination tests, t and F tests with SmartPLS software. The results of this data processing showed that X1, X2, X3 were able to predict the variability of construct Y by 74.9%, and the remaining 25.1% was explained by other constructs outside those studied in this study, with overall passengers feeling quite satisfied with the relationship between variables at Soekarno-Hatta airport.